Studi Identifikasi Nilai-nilai Karakter dalam Cerita Rakyat Masyarakat Rejang Kabupaten Lebong - Likardo, Reki (JURIDIKDAS, 2024)
This study aims to describe the types of folklore that developed in the Rejang society, Lebong Regency, and describe the character values in folklore identified in Lebong Regency. This research uses qualitative research with survey method. The main instrument in this study is the researcher himself and is assisted by supporting instruments in the form of interview sheets and documentation. Data collection techniques used in this study were interviews and documentation. The data obtained were analyzed through data reduction, data display (data display), and drawing conclusions. The results of the study collected fourteen folk tales found in three areas in South Lebong District. Based on the identification results, it can be concluded that, from fourteen folk tales adapted to the types of folklore, they were obtained, namely: four folk tales with the type of myth, five folklores with the type of legend, and five folklores with the type of fairy tale. Based on the results of the identification, it can be concluded that the character values found in the folklore of the Rejang society, Lebong Regency, obtained nine character values, namely: honest, hard work, creative, democratic, curiosity, respect for achievement, care for the environment, social care, and responsibility.